Recurrent ovarian cancer with BRCA reversion: a case study and comprehensive literature review - Karandikar, Sadanand; Joon, Himanshi; Puntambekar, Shailesh; Nehra, Amit; Chaudhari, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Herein, this report presents the case of a 48-year-old female with a history of breast cancer (2013) and subsequent high-grade epithelial ovarian cancer (2020), illustrating the complex evolution of therapeutic resistance in BRCA1-mutated malignancies. Following initial response to paclitaxel-carboplatin chemotherapy and complete surgical debulking, the patient experienced multiple disease relapses transitioning from platinum-sensitive to platinum-resistant states. Comprehensive molecular profiling via Tempus xF+ next-generation sequencing revealed a pathogenic BRCA1 mutation alongside a secondary BRCA1 reversion mutation, conferring partial restoration of homologous recombination repair and resistance to both platinum-based chemotherapy and PARP inhibitors. Subsequent therapies, including pemetrexed and liposomal irinotecan, were employed with limited success. This case underscores the dynamic molecular evolution of recurrent ovarian cancer under therapeutic pressure and highlights the critical role of serial genomic profiling in guiding personalized treatment strategies. Emerging approaches targeting alternative DNA repair mechanisms and novel antibody–drug conjugates may hold promise for overcoming resistance in BRCA-mutated, therapy-refractory ovarian cancer.